Non‐polar extracts of Nicotiana glauca (Solanaceae) induce apoptosis in human rhabdomyosarcoma cells - Musso, Florencia Antonella (2020)
Rhabdomyosarcoma (RMS) is the most common soft-tissue tumour in children andadolescents. It originates in normal skeletal muscle from myogenic cells that have failed to fully differentiate, and it usually has a poor prognosis. Current RMS therapy has many adverse effects. Hence, new treatments are needed. Various pharmacological properties, such as analgesic, antineoplastic, antimicrobial, and antiparasitic properties, have been demonstrated in species of the Solanaceae family. We performed ethanolic extraction from leaves of Nicotiana glauca (Solanaceae), and the extract was successively partitioned with n-hexane, chloroform, and ethyl acetate. We evaluated the effects of extracts on RMS cells, and we found that the extracts trigger apoptosis. By bio-guided fractionation assays, we identified the apoptotic agents. Morphological assessment after apoptotic cell induction of cultured cells, mitochondrial and nuclear morphology by Mitotracker, and 4,6-diamidino-2-phenylindole (DAPI) staining, respectively, were analysed in fluorescent microscopy. The capacity of the cells to migrate or proliferate was analysed by the Petit assay, followed by methylene blue staining. NMR and GC-MS spectrometry were used to identify palmitic acid and scopoletin as the phytochemicals responsible for the observedeffects. These results indicate that these compounds are apoptotic inducers and they could be useful as chemotherapeutic agents against muscle tumours.